2021
DOI: 10.1097/ta.0000000000003226
|View full text |Cite
|
Sign up to set email alerts
|

In-house versus on-call trauma surgeon coverage: A systematic review and meta-analysis

Abstract: BACKGROUND:A rapid trauma response is essential to provide optimal care for severely injured patients. However, it is currently unclear if the presence of an in-house trauma surgeon affects this response during call and influences outcomes. This study compares in-hospital mortality and process-related outcomes of trauma patients treated by a 24/7 in-house versus an on-call trauma surgeon. METHODS:PubMed/Medline, Embase, and CENTRAL databases were searched on the first of November 2020. All studies comparing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…(median 2.7 h (IQR 1.6-4.0) vs 2.1 h (1.5-3.7) p < 0.01) There was also a significant decrease in time from the ED (Emergency Department) to the intensive care unit (ICU) for patients directly transferred to the ICU (median time of 1.4 h (IQR 1.1-2.5) vs 1.2 h (IQR 1.0-1.6) (p < 0.01) and almost doubling of the percentage of patients who reached the operation room within 30 minutes (4.8% vs 8.0%) [14]. Moreover, a recent systematic of de la Mar et al, [15] revealed that ten out of sixteen included studies found at least one process related outcome to be improved after the implementing an in-house trauma surgeon attendance strategy. Furthermore, 7490 severely injured patients were included in a meta-analysis from eight different studies and severely injured patients treated by on-site surgeons had a significantly lower mortality rate when compared to trauma surgeons on call (risk ratio 0.86, 95% confidence interval 0.78 to 0.95; P < 0.01).…”
Section: Discussionmentioning
confidence: 91%
“…(median 2.7 h (IQR 1.6-4.0) vs 2.1 h (1.5-3.7) p < 0.01) There was also a significant decrease in time from the ED (Emergency Department) to the intensive care unit (ICU) for patients directly transferred to the ICU (median time of 1.4 h (IQR 1.1-2.5) vs 1.2 h (IQR 1.0-1.6) (p < 0.01) and almost doubling of the percentage of patients who reached the operation room within 30 minutes (4.8% vs 8.0%) [14]. Moreover, a recent systematic of de la Mar et al, [15] revealed that ten out of sixteen included studies found at least one process related outcome to be improved after the implementing an in-house trauma surgeon attendance strategy. Furthermore, 7490 severely injured patients were included in a meta-analysis from eight different studies and severely injured patients treated by on-site surgeons had a significantly lower mortality rate when compared to trauma surgeons on call (risk ratio 0.86, 95% confidence interval 0.78 to 0.95; P < 0.01).…”
Section: Discussionmentioning
confidence: 91%
“…Besides the benefits, an experienced trauma team leader brings during the trauma resuscitation, their additional experience for managing the severely injured may also have beneficial implications for the process after the resuscitation in the trauma bay, such as time to the operation room or additional imaging. For the management pace of severely injured patients, a recent systematic review showed that ten out of sixteen included studies found at least one process-related outcome was improved after implementing an in-house attendance policy for trauma surgeons instead of the on-call attendance policy during which less experienced surgical residents act as the house officer [ 23 ].…”
Section: Organizationmentioning
confidence: 99%
“…Some authors did not demonstrate any reduction on mortality [ 1 , 2 ], whereas others provided arguments for a decrease in preventable deaths [ 3 ]. A recent review on this topic suggested that a 24/7 in-house trauma surgeon was associated with reduced mortality for severely injured patients in a level-1 trauma center setting [ 5 ].…”
Section: Introductionmentioning
confidence: 99%